Bridging Molecular Docking to Molecular Dynamics to Enlighten Recognition Processes of Tailored D-A/D-A-D Types' AIEgens with HSA/BSA - Harun Nalçakan; Gülbin Kurtay (Journal of Advanced Research in Natural and Applied Sciences)
Fluorescence imaging-assisted photodynamic therapy (PDT) allows accurate tumor visualization and potentially prevents long-term side effects of cancer. Therefore, the development of photosensitizers emitting light, particularly in the near-infrared region (NIR), is essential for enhancing the efficacy of cancer therapy. On this premise, the formation of a stabilized complex between an organic dye and a target macromolecule improves fluorescence efficiency. In this scope, we performed a detailed molecular dock-ing study of Donor (D)-Acceptor (A) or D-A-D type luminogens with two blood proteins; namely bovine serum albumin (BSA) and human serum albumin (HSA), which appeared as robust carriers of several pharmaceuticals against preliminary cancer diseases. Our results revealed that the binding scores of the Dn-An or Dn-An-Dn:BSA complexes ranged from -8.5 to -11.7 kcal/mol while Dn-An or Dn-An-Dn:HSA complexes showed scores varying from -8.4 to -10.5 kcal/mol. Subsequently, molecular dynamics simu-lations were also performed for the best-docked ligands: macromolecule complexes; namely D1A1D1:BSA and D1A1:HSA, to enlighten various structural parameters. Based on the predicted root-mean-square deviation (RMSD) values (on average), the D1A1D1:BSA complex was found to be 0.319 nm, while the D1A1:HSA complex was determined as 0.284 nm. In addition, the root-mean-square fluctuations (RMSF) analyses (on average) revealed that D1A1D1:BSA (0.152 nm) was slightly more flexible than D1A1:HSA (0.160 nm).